Toward resource independence – Why state-owned entities become multinationals: An empirical study of India’s public R&D laboratories - Choudhury, Prithwiraj; Khanna, Tarun (Journal of International Business Studies, 2014)
In this paper, we build on the standard resource dependence theory (RDT) and its departure suggested by Vernon to offer a novel explanation for why state-owned entities (SOEs) might seek a global footprint and global cash flows: to achieve resource independence from other state actors. In the context of SOEs, the power use hypothesis of standard RDT can be used to analyze the dependence of SOEs on other state actors, such as government ministries and government agencies that have ownership and control rights in the SOE. Building on Vernon, we argue that the SOE can break free from this power imbalance and establish resource independence from other state actors by becoming a multinational firm and/or by generating global cash flows. We leverage a natural experiment in India and outline both quantitative and qualitative evidence from 42 Indian state-owned laboratories to support this argument.